PP-001 Development of method and process validation for quantitative analysis of ibuprofen suppositories. (24th February 2014) - Alihodzic, D; Rexin, I; Goerke, A; Baehr, M; Langebrake, C; Loebering, M
Abstract : Background: Ibuprofen suppositories are produced as bulk ware by the hospital pharmacy. According to the recently amended German regulation, 'Apothekenbetriebsordnung', which entered into force on 12 June 2012, supplementary quality controls regarding bulk ware have been requested in § 8: For non-validated manufacturing processes, each batch of bulk ware has to be analysed for uniformity of content. Neither the German nor the European Pharmacopoeia provides instructions for the quantitative analysis of formulations. Purpose: The aims of this study were (1) to develop and validate an appropriate method for the quantitative analysis of ibuprofen suppositories, which fulfils the conditions set out in the European Pharmacopoeia as well as the Good Manufacturing Practice Guidelines and (2) to validate the manufacturing process. Materials and methods: A literature research was performed to find an adequate quantification method for ibuprofen suppositories. To validate the method, the accuracy, precision, specificity, linearity and range were evaluated, according to the Guidelines of International Conference on Harmonisation (ICH). In the following validation of the process, a risk analysis was carried out to determine the critical parameters and a quantitative analysis of the suppositories was conducted. Results: The method developed to validate the ibuprofen content involved a procedure for the dissolution with dichloromethane and methanol and quantification of ibuprofen using an acidimetric titration. It was successfully validated according to the requirements of ICH Guidelines. Regarding process validation, all of the individual contents of the suppositories produced by four staff members were within the required range of 85–115% in terms of uniformity of content. Measures arising from the risk analysis complied with the predefined specifications. Conclusions: Validation of the method and process developed resulted in suitable quality control of the manufacturing process of ibuprofen suppositories. This approach can be adopted by other hospital pharmacies and may serve as an example for the development of further method and process validations in the future. No conflict of interest.